Foreign language anxiety and nursing clinical communication competence in Indonesian pre-elementary nursing students: A mixed methods study - Putri, Diannike; Sumarni, Tri; Sukmawati, Ida Dian; Kristanto, Barlian (Yayasan Mitra Persada Nusantara, 2025)
English communication competence is essential for nursing professionals in global healthcare settings. However, language anxiety can hinder the acquisition of these skills, particularly among nursing students learning English for Specific Purposes (ESP). Limited research exists on language anxiety in ESP learning for nursing, especially in Asian contexts like Indonesia. This study aimed to examine the relationship between language anxiety and specific nursing communication performance among pre-elementary level nursing students in Indonesia, focusing on a vital-signs checking task. An explanatory sequential mixed methods design was employed. Sixteen pre-elementary level nursing students from Harapan Bangsa University, Indonesia, completed the Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire and participated in a vital-signs checking role-play task. Performance was evaluated using an adapted assessment rubric. Quantitative data were analyzed using descriptive statistics and Pearson correlation coefficients. Participants demonstrated moderate levels of language anxiety (M = 3.00, SD = 1.00), with higher anxiety related to communication apprehension and fear of negative evaluation. A significant negative correlation was found between language anxiety and overall communication performance (r = -0.58, p < 0.05). Stronger negative correlations were observed between anxiety and language accuracy (r = -0.62), fluency (r = -0.54), and pronunciation (r = -0.57), while no significant correlations were found with content accuracy or nonverbal communication. This study provides empirical evidence for the detrimental impact of language anxiety on nursing students' communication performance in clinically relevant tasks. The findings underscore the need for targeted interventions to address language anxiety in ESP learning for nursing, considering individual learner profiles and the specific challenges of communication in healthcare contexts.